Antihyperlipidemic Potential of Polyphenol and Glycoside Rich Nerium oleander Flower against Triton WR-1339-Induced Hyperlipidemia in Experimental Sprague Dawley Rats. (27th August 2012) - Gayathri, V.; Ananthi, S.; Vasanthi, Hannah R.
Abstract : Nerium oleander Linn. (NO), an evergreen cardiac glycoside-rich shrub is used as folklore medicine in China to treat many diseases. It exhibits a wide spectrum of bioactivities but there were not much scientific reports on the bioactivity of N. oleander flowers. In the present study, we have evaluated the toxicity profile of the 50% hydroethanolic extracts of Nerium oleander flowers (ENO) using in vitro brine shrimp lethality assay and MTT cytotoxicity assay and in vivo acute toxicity test as per the OECD guidelines. The antihyperlipidemic activity of the ENO was also studied using Triton WR-1339-induced hyperlipemic rats and compared with standard Atorvastatin. In vitro brine shrimp, MTT cytotoxic assay, and in vivo acute toxicity assays showed a wide safety margin which has been evidenced through its lethal concentration (LC50 : 795.46  μ g/mL) and growth inhibition (GI50 : 993.60  μ g/ml) values. Plasma lipids and lipoproteins were significantly elevated by the intraperitoneal injection of Triton WR 1339 in hyperlipidemic rats at 6th and 24th hour. ENO pretreatment showed a significant ameliorative action on elevated lipids and lipoproteins in a dose-dependent manner when compared to standard. Altogether, the results prove that Nerium oleander flowers are not toxic at the tested doses and exhibit antilipimic activity.